The enteric microbiota in health and disease - Guarner, Francisco (Henry Stewart Talks, 2011)
Impact of the microbiota on host anatomy and physiology, Primary functions of the gut microbiota, Induction of the immune system, The 'Old Friends' hypothesis, Microbiota dysfunction and disease, Composition of the colonic microbiota, The international human microbiome consortium, The human metagenome, Conclusions